Study on Surface Runoff Estimation for Puzhal Lake Using GIS - Subramani, T; Sasikala, S (International Journal of Engineering and Technology, 2018)
To make greater in grow in land use/cover have lead to environment change in Puzhal Lake and flooding in under areas. environmental condition and the utilization of apparatus for cultivating in the zone are causing issues of soil degradation. Runoff is one in every of most vital hydrological factors that are utilized as a part of numerous common works, anticipating ideal utilization of supplies, sorting out waterways and cautioning flood. Appropriate to the spatial and transient fluctuation of the variables associated with surface runoff, the use of a displaying plan in a GIS ecological gives a productive way to deal with decide zones of concern. Three surface runoff models were connected including: the record strategy, SCS bend number technique, a semi physical way to deal with evaluate the dissemination of surface runoff. The customary SCS-CN strategy for computing the composite curve number devours a noteworthy part of the hydrologic displaying time. Hence, geographic data frameworks (GIS) are presently being utilized as a part of mix with the SCS-CN technique.Â Â
Keywords: Surface; Runoff; Estimation; Puzhal Lake and GIS.